How is disease progress in Friedreich's ataxia best measured? A study of four rating scales. Issue 4 (20th October 2006) - Fahey, M C; Corben, L; Collins, V; Churchyard, A J; Delatycki, M B
Abstract : Background: Friedreich's ataxia (FRDA), the most common genetic cause of ataxia, is characterised by progressive neurodegeneration and cardiomyopathy. Initial treatments are likely to slow progression rather than reverse morbidity. An appropriate and sensitive scale to measure disease progress is critical to detect the benefit of treatments. Objective: To compare the Friedreich Ataxia Rating Scale (FARS) with other scales proposed as outcome measures for FRDA. Methods: 76 participants were assessed with the FARS and the International Cooperative Ataxia Rating Scale (ICARS) and 72 of these participants were also assessed with the Functional Independence Measure and the Modified Barthel Index. 43 participants had repeat measures at an interval of 12 months. Sensitivity and responsiveness were assessed using the effect size for each measure and the sample size required for a placebo-controlled clinical trial. Results: The FARS showed a high correlation with the other three measures. A significant change in the score over 12 months was detected by the FARS, the International Cooperative Ataxia Rating Scale and the Functional Independence Measure. The FARS had the greatest effect size and requires fewer patients for an equivalently powered study. Conclusions: Of the scales assessed, the FARS is the best to use in clinical trials of FRDA. This is based on effect size, and power calculations that show that fewer participants are required to demonstrate the same effect of an intervention. Further work is required to develop more sensitive and responsive instruments.